O processo de colaboração nos trabalhos de coautoria em ambientes virtuais de aprendizagem - Mandaji, Mônica dos Santos (2011)
The current research is connected to the Post-Graduate Program in Education: Curriculum at Catholic University of Sao Paulo (PUC-SP) in the research group New Technologies in Education . This study proposes to analyse the development of the collaboration process in coauthoral works developed in learning management systems. The research aimed to contribute for the evolution of the mark which recognizes the importance of collaboration in processes of teaching and learning in learning management systems through the construction of categories and models for the analysis of collaborative practices. The theoretical concepts were established upon two themes of origin: the concept of collaboration itself, with references, among others, in Amoretti; Simon; Maturana and Varela; Fiorentini; Johnson and Jonhson; and the evolution of communication, the consequent characterization of the information society and the evolution of the Web 2.0 as an effective possibility to use in processes of teaching and learning upon the concepts established by Ausubel; Barbero; Boavida and Ponte; Castells; Cunningham, Schons among others. The research universe was constituted of courses in continuous education and undergraduate distance learning courses, with focus on the following cases: the course Distance Learning and Musical Education developed by the Association of Friends of the Guri Project of the State Department of Culture of São Paulo and the course Culture in the space of diversity, sustainable development and inclusion CEDSI-Pe taught within the undergraduate Pedagogy course of UAB Ufscar Open University of Brazil at Federal University of São Carlos. Its analysis was made through the study of the relations established by the participants in the development of activities of coauthoring. As methodology it was used the bricolage method, since it comprehends an extensive group of possibilities and admits the use of techniques of qualitative and quantitative analysis with an observation directed towards the practices of the individual upon which one aims to break with the reductionism, the idea of installments, the fragmentation and the scientific neutrality of positivist methods, according to Kincheloe and Berry. Identified the repetition of actions in the relationships between individuals in the process of development of coauthoral activities it is possible to evidentiate as main contribution that the development of models for analysis categories may make it easier to accompany this process for teachers and collaboration managers in virtual learning spaces; and that the categorization of relationships makes it possibile for an evolution of the quantitative analysis for its qualification; with that new possibilities are open, such as the development of specialist systems in the field of Artificial Intelligence